A case report and literature review: an intra-abdominal epithelioid neoplasm with EWSR1::CREB fusions originating from the kidney - Zheng, Zhen; Liu, Enjie; Yang, Minglei; Liu, Xiu; Wei, Jianguo (Frontiers in Oncology, 2025)
BackgroundEWSR1::CREB fusion is a newly identified group of aggressive tumors with epithelioid morphology and multiple growth patterns. These tumors are often located in the abdominal cavity and frequently show cytokeratin expression immunohistochemically. This invasive epithelioid soft tissue tumor has a remarkable preference for mesothelial-lined cavities, with rare extension into intra-abdominal organs such as the kidney. Given its rarity, early diagnosis and treatment are crucial. Currently, the diagnosis and treatment of this disease pose significant challenges.Case demonstrationA 36-year-old male patient with no significant past medical history was admitted with a mass in the left kidney. Computed tomography showed a mass in the lower left kidney near the renal portal, and chromophobe carcinoma was suspected. The patient subsequently underwent a partial nephrectomy. The case was initially diagnosed as a malignant tumor with epithelial and mesenchymal components. RNA sequencing and FISH of the kidney mass confirmed the diagnosis of intra-abdominal epithelioid neoplasms with EWSR1::CREB fusions originating from the kidney. The patient did not undergo any adjuvant therapy and has been followed up for 14 months. He is currently in good condition.ConclusionIntra-abdominal epithelioid neoplasm with EWSR1::CREB fusions originating from the kidney is rare. The remarkable morphological features of the case presented here further confirm the significant morphological heterogeneity of tumors characterized by EWSR1::CREB fusion and expand the morphological spectrum of malignant epithelioid tumors with EWSR1::CREM rearrangements originating from the kidney. Additionally, neoplastic cells encircled native renal tubules, demonstrating an infiltrating growth pattern, and the renal tubules proliferated significantly, which may lead to misdiagnosis as other tumors that exhibit biphasic morphology.